Solitary fibrous tumor of the pleura with marked cystic degeneration: a case report - Takuya Watanabe; Masayuki Tanahashi; Eriko Suzuki; Naoko Yoshii; Kensuke Chiba; Hiroyuki Tsuchida; Shogo Yobita; Suiha Uchiyama; Kensuke Iguchi; Hiroshi Ogawa; Hiroshi Niwa (Surgical Case Reports)
Abstract Background Solitary fibrous tumor of the pleura (SFTP) is a mesenchymal tumor, and computed tomography typically shows SFTPs as well-defined lobulated masses. We herein report a case of SFTP with cystic degeneration of the entire tumor. Case presentation The patient was a 67-year-old Japanese man who was referred to our hospital for an abnormal shadow on a chest X-ray. Computed tomography showed a 9-cm cystic tumor in the lower left lobe, with small nodules aggregated in the cyst. Pulmonary aspergillosis was suspected, and left basal segmentectomy was performed. A pedunculated cystic tumor was connected to the pleura with a stalk, and white polypoidal masses were found within the cystic tumor. Microscopy revealed uniform fibroblastic spindle cell proliferation and marked cystic degeneration, the cyst walls were formed of the same tumor cells. Immunohistochemical staining revealed that the tumor cells were positive for CD34, CD99, and BCL2. Based on these findings, the tumor was diagnosed as SFTP with cystic degeneration. Conclusion We experienced an extremely rare case of atypical SFTP with cystic degeneration.